Opposition political discourse as an element of political training - Frank Mejía Guzmán (Ratio Juris, 2018)
The understanding of the analysis of the opposition’s political discourse will be done at the time under the argumentative approach, using elements of hermeneutical understanding or a structuralism that allows us to delve into that tool of power that governments, the opposition, or the ordinary citizen have to achieve intervene pragmatically the mediated political exercise. To understand the dynamics of a discourse that on the one hand seeks to establish a position contrary to the guidelines of the current government and then, through that same discourse, to finish delimiting the way we should understand the political, the way we should perceive the other in opposition, that other one that at the proper moment of the mediatization of the discourse acquires the skin of the government of the day, because it is the government in office. The intention is in some way to demonstrate how the political discourse of opposition is nothing other than an interest in achieving permeate the gaze of those who, without theoretical elements, tries to establish his own political analysis from the everyday, in other words, discourse as a tool for political training.